Дослідження методів побудови 3D моделей у веб-додатках за допомогою React - Гладченко, О. О. (ХНУРЕ, 2024)
This work is devoted to assessing various methods of building three-dimensional (3D) models in web applications using the React library. The use of 3D models in the web environment is becoming increasingly popular, especially in the fields of data visualization, gaming and experimental design. This research compares different approaches to creating 3D models in the web environment, focusing on their efficiency, productivity, and accessibility for developers. Using React as the main tool for developing web applications, we explore how this framework can be used to build and interact with 3D models in an online environment. The results of this study indicate the potential benefits and limitations of different approaches to integrating 3D graphics into web applications using React.
Keywords: 3D модель; веб-додаток; React